Avifaunal disarray: quantifying models of the occurrence and ecological effects of a despotic bird species. Issue 4 (14th January 2015) - Thomson, James R.; Maron, Martine; Grey, Merilyn J.; Catterall, Carla P.; Major, Richard E.; Oliver, Damon L.; Clarke, Michael F.; Loyn, Richard H.; Davidson, Ian; Ingwersen, Dean; Robinson, Doug; Kutt, Alex; et al.
Abstract Aim Strongly interacting species have disproportionately large ecological effects relative to their abundances or biomass. We previously developed two conceptual models that described how one such strong interactor, the Australian bird the noisy miner Manorina melanocephala: (1) establishes resident high‐density and hyperaggressive colonies and (2) in doing so, affects other biota and ecosystem processes. Here, we evaluate parts of those models relating to noisy miner habitat preferences and effects on bird assemblages using data from across the geographical range of the miner. Location Eastern Australia. Methods Avian‐assemblage data were compiled for 2 128 survey transects (distributed over > 1.3 × 106 km2) and were linked to variables reflecting productivity, local habitat structure and landscape context. Predictors were chosen based on the models, although detailed data for some variables were unavailable at such large scales. We used hierarchical Bayesian models that included observation models to account for different survey effort coupled with potentially nonlinear, spatially‐explicit process models. Conclusions Noisy miner densities increased with proximity to forest edges (higher densities on forest edges and open sites), in low rainfall areas, and in vegetation dominated by trees with blade‐shaped rather than needle‐shaped leaves. The presence of noisy miners at even relatively small densities (> 0.6 individuals ha−1) depressed both species richness and the abundances of smaller (< 63 g) bird species, by 50% on average. There were positive associations between densities of noisy miners and the abundance and richness of larger‐bodied (> 63 g) bird species. In areas with higher mean rainfall, the associations between noisy miners and small‐ and large‐bird species were more negative and less positive, respectively.